A hydroponic vegetable business management approach in holistic good agricultural practices in Thailand - Ruploet, Ponkamon; Kaewhanam, Kathanyoo; Phansoomboon, Sayan; Piriyaphattarakit, Anan (Frontiers in Sustainability, 2024)
Good agricultural practices (GAP) are guidelines designed to ensure the production of high-quality agricultural products that meet specified standards while optimizing resource use. This study aimed to examine the challenges and success factors in implementing a holistic system of GAP in hydroponic vegetable business management and to enhance the efficiency of Thailand’s policies on safe agricultural standards. In this study, a qualitative research methodology was used, using in-depth interviews, semi-structured interviews, and observations with 36 intermediaries and consumers in Thailand. Data analysis was conducted using descriptive statistics. The study revealed that key challenges to successful GAP implementation include unsupportive government policies and a lack of in-depth knowledge among farmers on how to effectively apply GAP principles. For successful implementation, it is crucial that farmers who lead these efforts thoroughly understand the methods and prioritize safe and proper farming practices. This knowledge can then be leveraged to prepare and educate farmers, producers, and entrepreneurs to produce high-quality agricultural products. GAP for crops include policies, benchmarks, and audit processes that adhere to international standards, providing a framework for controlling and promoting product quality throughout the agricultural production process, including post-certification maintenance. The study suggests that cooperation across all relevant sectors, from upstream to downstream, is essential for the successful implementation of GAP. Such collaboration would significantly enhance the quality and safety of Thailand’s agricultural standards.